MENINGKATKAN PRESTASI BELAJAR SISWA MATERI OPERASI HITUNG FPB, KPK BILANGAN BERAKAR KUBIK DENGAN MIND MAPPING PADA SISWA KELAS VI SDN 002 BANGUN PURBA TAHUN PELAJARAN 2015/2016 - ., Liswati (Edu Research, 2016)
This study uses action research (action research) as much as two rounds. Each round consists of four phases: design, activities and observations, reflections, and revision. This research target is class VI SD Negeri 002 Bangun Purba. The data obtained as the result of formative tests, observation sheet teaching and learningactivities. From the analyst found that student achievement increased minimum completeness criteria from the first cycle to the third cycle, namely, the first cycle (34.62%) and the second cycle (76.93%). Cycle III 100%. Conclusions from this research is a model of teaching mind mapping can be a positive influence on achievement, interest, attention, and participation, motivation to learn Class VI SD Negeri 002 Bangun Purba and this model can be used as an alternative learning mathematics.